Is the serving size and household measure information on labels clear and standardized? Analysis of the labels of processed foods sold in Brazil - Nathalie Kliemann; Marcela Boro Veiros; David Alejandro González-Chica; Rossana Pacheco da Costa Proença (Fundação Oswaldo Cruz (FIOCRUZ), 2014)
This study aimed to analyze the household measures reported on labels of processed foods, taking into account their adequacy with the type of food and their relationship with the declared serving size. We analyzed the labels of processed foods for sale in a Brazilian supermarket. Serving sizes were assessed according to the parameters of the Brazilian law, and household measures were assessed according to the term used. A chi-square heterogeneity test was performed, and a p value of <0.05 was considered indicative of statistical significance. We analyzed 1,102 processed foods and found that 72% declared the exact reference serving size prescribed by the Brazilian law. We found inappropriate household measures with regard to the way foods are customarily consumed (e.g., 2 ½ cookies) as well as subjective (e.g., 2 pieces) or incomplete (e.g., 1 spoon) measure terms. Household measures expressed as fractions were greater among products with measures that referred to the product's total weight (e.g., ½ package) and with serving sizes that complied with the Brazilian law (p < 0.001). Therefore, the serving size and household measure information on the labels of Brazilian processed foods are neither appropriate nor standardized. Consequently, this could complicate consumers' understanding and use of this information.